Entrepreneurial behaviors and perceptions influencing business decisions among rural women in Kakamega County, Kenya - Ondiba, Hesborn Andole; Matsui, Kenichi (Kasetsart Journal of Social Sciences, 2021)
This paper examines factors that influence rural women’s decisions when starting and running businesses in Kakamega County, Kenya. It seeks to understand how their socio-demographic variables such as entrepreneurial experience, education, age and labor availability influence their business behavior and performance. A questionnaire survey was administered among 153 rural women entrepreneurs in Kakamega County. We found that rural women chose businesses that were closely related to their traditional gender roles. About 53 percent of the respondents tended to choose small farm retail businesses that required only basic management skills with affordable capital. About 56 percent of them decided to set up their enterprises near their homes where access was by foot. 84 percent of rural women preferred smallscale, informal businesses. Chamas, women’s informal social network organizations, supported our respondents through training and capital provision. With regards to business operation, we found that the availability of labor and education level significantly influenced rural women’s business performance. Respondent’s with a higher education level tended to be innovative and were more confident when making decisions in their businesses.